Institusi Pendidikan dan Pengembangan Karakter Bangsa - Murtadha (Enlightenment Publishing, 2023)
Educational institutions are official institutions that play an important role in passing on knowledge, culture and religion as well as being the main institutions that hold responsibility for the formation and development of the character of the nation's generations. Educational institutions have long been known by the world's population as institutions that inherit values ​​and knowledge so that generations are able to take responsibility for their every action. Education is the learning of knowledge, skills, and habits of a group of people that is transferred from one generation to the next. In Law no. 20 of 2003 has stated that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves and society, nation and state. The good civilization of a nation can be seen from the number of problems experienced by that nation, or it can be seen from the level of prosperity of its people. The younger generation is the party who most determines the condition of a nation in the future. A good and quality young generation can be created through the education process. Through education, we will create a generation that has great abilities in overcoming various problems of a nation.